Why do chitons curl into a ball?. (2nd October 2019) - Sigwart, Julia D.; Vermeij, Geerat J.; Hoyer, Peter
Abstract : Many animals with external armour, such as hedgehogs, isopods and trilobites, curl into a protective ball when disturbed. However, in situations where predators would engulf an exposed animal whole, regardless of position, conglobation may provide limited added defence and the benefits were previously unclear. We show that polyplacophoran molluscs (chitons) are three times less likely to spend time curled into a ball in the presence of a predator. When the cue of a potential predator is present, animals instead spend significantly more time in active, high risk, high reward behaviours such as arching, balancing on the head and tail ends of their girdle and pushing the soft foot up into an exposed position. Arching increases vulnerability, but also can increase the likelihood of rapidly encountering new substratum that would allow the animal to right itself. In some other animals, the ability to roll into a ball is associated with rolling away from danger. Curling into a ball would improve mobility, to be rolled on to a safer position, but reattachment is the higher priority for chitons in the face of danger.